Oscillation of solutions to a generalized forced nonlinear conformable fractional differential equation (2019)
By using averaging functions, we present some new oscillation criteria for the solution of a generalized forced nonlinear conformable fractional differential equation. The results obtained here extend and improve on some existing results. Examples are also given to show the validity of our results.